2007
DOI: 10.1111/j.1445-5994.2007.01435.x
|View full text |Cite
|
Sign up to set email alerts
|

Current management of acute coronary syndromes in Australia: observations from the acute coronary syndromes prospective audit

Abstract: There appears to be an 'evidence-practice gap' in the management of ACS, but this is not matched by an increased risk of in-hospital clinical events. Objective evaluation of local clinical care is a key initial step in developing quality improvement initiatives and this study provides a basis for the improvement in ACS management in Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
56
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 22 publications
9
56
3
Order By: Relevance
“…These secondary prevention strategies have been shown to be critical to management of the underlying disease and prevention of recurrent hospital admission and death [11][12][13] . In spite of the evidence, existing literature indicates that adherence to secondary prevention strategies is suboptimal [12][13][14] . In particular, only about 30% of eligible patients access CR programs in Australia and the United States (US) 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…These secondary prevention strategies have been shown to be critical to management of the underlying disease and prevention of recurrent hospital admission and death [11][12][13] . In spite of the evidence, existing literature indicates that adherence to secondary prevention strategies is suboptimal [12][13][14] . In particular, only about 30% of eligible patients access CR programs in Australia and the United States (US) 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…8 While it appears that adherence to clinical guidelines is highest among STEMI sufferers, only half of NSTEACS-HR patients underwent guideline-recommended invasive management. 5 This is lower than rates found in other international registries, reflecting not only patient access and preference for treatment, but also lenient risk stratification by decision-making teams. 9 This snapshot of the experience of ACS in Australia highlights an inability to marry current ACS guidelines with risk assessment tools in the clinical approach to ACS.…”
Section: Guidelines Adjuvant Tools and The Australian Experience Of mentioning
confidence: 81%
“…5 The authors identified varying compliance with guideline-recommended pharmacotherapies, reporting higher rates of aspirin and statin use; moderate rates of clopidogrel, beta-blocker and ACE-inhibitor/angiotensin receptor antagonist use; and low rates of glycoprotein IIb/IIIa inhibitor use. Regarding invasive management, the study found suboptimal rates of reperfusion therapy for STEMI across both rural and metropolitan populations.…”
Section: Guidelines Adjuvant Tools and The Australian Experience Of mentioning
confidence: 99%
See 2 more Smart Citations